Depelovment of an Interactive E-module using the Problem Based Learning Approach for the Topic of Systems of Linear Equations in Two Variables - Rizky, Astri Rully; Pebriantika, Leni; Susila, Heni Rita (Program Magister Teknologi Pendidikan Universitas Jambi, 2026)
This study aims to develop an interactive e-module based on the PBL approach for teaching Systems of Linear Equations in Two Variables. The study employed a Research and Development (R&D) design using the Dick and Carey model, adapted into eight stages, including needs analysis, instructional design, material development, and formative evaluation. The developed e-module integrates multimedia elements and PBL syntax to support student-centered learning and problem-solving skills. The product was evaluated through expert validation, one-to-one evaluation, small group evaluation, and field trials involving junior high school students. The validation results showed that the e-module achieved a high level of validity, with an average score of 88%, indicating that it is highly appropriate in terms of content, instructional design, and media quality. The practicality of the e-module was also confirmed through one-to-one, small group, and field testing, with an average score of 89%, categorized as very practical. These findings indicate that the developed e-module is both valid and practical for use in mathematics learning. The integration of digital media and PBL provides an effective alternative to enhance student engagement and support problem-solving-oriented learning in secondary education. These findings indicate that the e-module is valid, practical, and effective, and can serve as an innovative digital learning medium to support student-centered learning in junior high school.